The Utilization of 360-Website as Authentic Materials in ESP: Opportunities and Challenges - Putu Tika Virginiya; Lastari, Ni Kadek Herna (Perspektif Ilmu Pendidikan, 2025)
This study aims to explore the utilization of 360-view web-based authentic materials in English for Specific Purposes (ESP) teaching and identify the opportunities and challenges it faces. The research method used is a qualitative approach with data collection techniques through observation, interviews, and questionnaires given to ESP students and lecturers. The results showed that using 360-view websites as authentic materials can increase student engagement, enrich the learning experience through interactive visualizations, and help them understand the real-world context in specific fields of expertise, especially in the hospitality sector. However, challenges include limited access to technology, lecturers' readiness to integrate digital media, and the need for more structured pedagogical guidance. The implication of this study highlights the need to develop more effective implementation strategies to maximize the benefits of 360 website-based authentic materials in ESP learning.